Evaluation of the Productivity Performance of BPR for Economic Resilience in East Java: A View from Efficiency and Technological Change - Aufa, Aufa; Maripatul Uula, Mimma; Maulida, Syahdatul (The International Journal of Financial Systems, 2023)
The Rural Bank (BPR) plays a crucial role in the Indonesian banking industry, particularly at the regional level, serving as an alternative financ-ing source for the unbankable population. This research aims to analyse the productivity levels of BPRs in East Java using the Malmquist Pro-ductivity Index (MPI) during the period from 2016 to 2022. The study sample comprises 30 BPRs in East Java. The analysis results indicate that the productivity of BPRs in East Java fluc-tuates from year to year. Moreover, during the COVID-19 pandemic, BPR productivity experi-enced a significant decline. The study provides recommendations for BPR management and regulators to pay more attention to BPR pro-ductivity and decision-making foundations.